MOTIVASI DALAM ISLAM - Azimi, Zul (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
This research aims to explore motivation and work motivation in Islam with an emphasis on aspects of pleasure in this world and the hereafter. Research findings reveal that motivation in Islam includes a holistic search for happiness, with the stipulation that worldly pleasures must be accompanied and balanced with obedience to Allah. This understanding guides Muslim individuals to achieve balance between the affairs of this world and the hereafter through the understanding that work is also a form of worship. Seeing work as worship provides a deeper dimension to motivation, not just limited to achieving material success or worldly achievements. On the contrary, work is considered as a means to obtain the blessings of life in this world and the hereafter. These findings provide a strong understanding that Muslim individuals can achieve a meaningful life balance through work, where their goals are not only focused on worldly success, but also on lasting happiness in the afterlife.